SARS-CoV-2 infection induces ZBP1-dependent PANoptosis in bystander cells - Bo Yang; Ao Hu; Tiantian Wang; Xiaolin Chen; Caina Ma; Xinyue Yang; Kai Deng (Proceedings of the National Academy of Sciences, 2025)
Virus-induced excessive inflammatory response is a key contributor to pathology in respiratory viral infections. However, the underlying mechanisms by which viral infection provokes intense inflammatory reaction and how sustained inflammation leads to tissue damage are not fully understood. Using severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as an example, our research demonstrates that SARS-CoV-2 infection can induce PANoptosis in bystander cells, contributing to the persistence of inflammatory responses. Specifically, the activation of cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) in infected cells leads to the secretion of 2′3′cGMP-AMP, TNF-α, and IFN-β. These molecules activate STING-induced autophagy-mediated ADAR1 degradation, resulting in the accumulation of Z-nucleic acid, which subsequently triggers ZBP1-dependent PANoptosis in bystander cells. Additionally, inhibiting the cGAS pathway or knocking out STING effectively reduces PANoptosis and alleviates the pathology associated with SARS-CoV-2 and influenza A virus infection in mouse models. Overall, our findings reveal the unexpected role of PANoptosis in bystander cells during SARS-CoV-2 infection as a mechanism driving pathological damage and persistent inflammatory responses. Targeting this process may offer a promising strategy to mitigate tissue damage in COVID-19 as well as other viral infections and inflammatory conditions.